Crop residue burning ails environment - Ankush, Ankush; Singh, Vikram; Prakash, Ram (Indian Farming, 2018)
It is a major threat to environment and soil too because this practice leads to loss of valuable nutrients like nitrogen (N), phosphorus (P), sulphur (S), and potassium (K) from the top layer of soil, make soil less fertile by abating level of beneficial microorganisms in soil, and make it difficult to use agriculture land in a long-run. It contributes towards the emission of greenhouse gases (CO2, N2O, CH4), air pollutants (CO, SO2, NOx, volatile organic compounds) particulate matter and smoke thereby possessing threat to human health.